Association of Vitrectomy for Floaters with Patient-Reported Quality of Life and Visual Disturbance : A Systematic Review of Randomized Controlled Trials and Primary Studies - Sri Adinda Ayu; Gunawan (The Indonesian Journal of General Medicine, 2026)
Introduction: Vitreous floaters (myodesopsia) can significantly impair patient-reported quality of life (QoL) and visual function. The role of pars plana vitrectomy (PPV) remains debated due to variability in study designs and outcome measures. This systematic review evaluates the association between PPV and patient-reported QoL and visual disturbance outcomes. Methods: A comprehensive search of adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines identified RCTs and primary observational studies reporting patient-reported outcomes after PPV, Nd:YAG vitreolysis, or observation for symptomatic floaters (minimum 3-month follow-up). Two independent reviewers assessed bias using Cochrane RoB 2.0 and Newcastle-Ottawa Scale. Narrative synthesis was performed. Results: Sixteen studies (2 RCTs, 14 observational; >4,019 eyes) were included. Patient satisfaction after PPV ranged from 84–94%. Best-corrected visual acuity improved by −0.08 logMAR (p<0.0001). NEI VFQ-39 scores increased by 19% (p<0.00001). Contrast sensitivity normalized post-PPV. YAG vitreolysis showed subjective improvement (54% vs. 9% sham) but no contrast sensitivity benefit. Retinal detachment rates were 1.5–10.9%; cataract progression reached 23.5% in phakic patients. Discussion: PPV significantly improves QoL, BCVA, and contrast sensitivity with acceptable safety using small-gauge techniques. YAG is a less invasive alternative for Weiss ring floaters but lacks functional CSF benefit. No large RCTs exist for PPV. Conclusion: PPV for symptomatic floaters is associated with meaningful improvements in QoL and visual function. Standardized, floater-specific PROMs and multicenter RCTs are urgently needed